Development and application of human skeletal muscle microphysiological systems. Issue 20 (5th September 2018) - Truskey, George A.
Abstract : Human microphysiological systems were developed to model skeletal muscle and nerve-skeletal muscle interactions. These systems can be applied to a number of major disease states involve skeletal muscle, including type 2 diabetes, muscular dystrophy, sarcopenia and cachexia arising from cancer or heart disease. Abstract : A number of major disease states involve skeletal muscle, including type 2 diabetes, muscular dystrophy, sarcopenia and cachexia arising from cancer or heart disease. Animals do not accurately represent many of these disease states. Human skeletal muscle microphysiological systems derived from primary or induced pluripotent stem cells (hPSCs) can provide an in vitro model of genetic and chronic diseases and assess individual variations. Three-dimensional culture systems more accurately represent skeletal muscle function than do two-dimensional cultures. While muscle biopsies enable culture of primary muscle cells, hPSCs provide the opportunity to sample a wider population of donors. Recent advances to promote maturation of PSC-derived skeletal muscle provide an alternative to primary cells. While contractile function is often measured in three-dimensional cultures and several systems exist to characterize contraction of small numbers of muscle fibers, there is a need for functional measures of metabolism suited for microphysiological systems. Future research should address generation of well-differentiated hPSC-derived muscle cells, enabling muscle repair in vitro, and improved disease models.